Penggunaan Media Loose Part Dalam Meningkatkan Kemampuan Berhitung Awal di TK Katolik St. Theresia Tomohon - Hasnawati Paputungan (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is motivated by the lack of early counting ability in children aged 5-6 years. The type of research used in this study is classroom action research referring to the Kemmis and Mc Taggart model which consists of four stages, namely: 1. Planning 2. Implementation 3. Observation 4. Reflection. With a research design using the loose part method. The research subjects were students at St. Theresia Catholic Kindergarten Tomohon, totaling 10 children. Data collection techniques used are observation and tests. The results showed a good change in cycle I, namely the results obtained reached 40%, while the results of cycle II obtained had increased to 100%. From the results obtained, it means that the objectives of this study have been successful. Based on the results of research and discussion, it can be concluded that loose part media in other early counting to improve children's learning outcomes